Circadian Clock Dysfunction and Psychiatric Disease: Could Fruit Flies have a Say? - Zordan, Mauro Agostino; Sandrelli, Federica (Frontiers in Neurology, 2015)
There is evidence of a link between the circadian system and psychiatric diseases. Studies in humans and mammals suggest that environmental and/or genetic disruption of the circadian system lead to an increased liability to psychiatric disease. Disruption of clock genes and/or the clock network might be related to the etiology of these pathologies; also, some genes, known for their circadian clock functions, might be associated to mental illnesses through clock-independent pleiotropy. Here we examine the features which we believe make Drosophila melanogaster a model apt to study the role of the circadian clock in psychiatric disease. Despite differences in the organization of the clock system, the molecular architecture of the Drosophila and mammalian circadian oscillators are comparable and many components are evolutionarily related. In addition, Drosophila has a rather complex nervous system, which shares much at the cell and neurobiological level with humans, i.e. a tripartite brain, the main neurotransmitter systems, and behavioral traits: circadian behavior, learning and memory, motivation, addiction, social behavior. There is evidence that the Drosophila brain shares some homologies with the vertebrate cerebellum, basal ganglia and hypothalamus-pituitary-adrenal axis, the dysfunctions of which have been tied to mental illness. We discuss Drosophila in comparison to mammals with reference to the: organization of the brain and neurotransmitter systems; architecture of the circadian clock; clock-controlled behaviors. We sum up current knowledge on behavioral endophenotypes which are amenable to modeling in flies, such as defects involving sleep, cognition, or social interactions and discuss the relationship of the circadian system to these traits. Finally, we consider if Drosophila could be a valuable asset to understand the relationship between circadian clock malfunction and psychiatric disease.